ANALISIS PERBANDINGAN PRAKTIK AKAD NIKAH DALAM MAZHAB HANAFI DAN SYAFI'I - Rani, Nur Sasi Septian; Ramadhani, Mutiara; Saputri, Nova Esa; Maharani, Ria; Fitri, Yuliza Aidil (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2025)
This research discusses the different views of the Hanafi and Shafi'i madhhabs regarding the role of the guardian in the implementation of the marriage contract. The main focus of the research is how the two madhhabs assess the importance of the guardian in determining the validity of marriage. In terms of theory, the Hanafi school of thought considers the guardian as a complementary condition of the contract, so that a woman who is an adult and has the right mind can marry herself on the condition of fulfilling the sekufu and giving the appropriate dowry. In contrast, the Shafi'i school of thought views the guardian as an important part that must be present for the marriage to be valid. The method used is a qualitative study with a literature approach and comparative analysis of various sources of Islamic law. The research findings show that this difference arose due to different social and cultural backgrounds at the time of the scholars. In conclusion, this difference affects women's rights and the role of the family in the marriage contract process. Understanding these differences is important so that marriage practices can be adapted to the social conditions and needs of today's society.